Staff Operational Guidelines On Dissemination Of Technical Assistance Information. (Policy Papers; Policy Paper ;, 2020)
The Staff Operational Guidelines on Dissemination of Technical Assistance Information have been updated to reflect the authority reserved to Fund management and TA recipients to provide explicit consent for the dissemination of TA information in scenarios not specifically envisaged in these guidelines.